Equity and Efficiency of Childcare Subsidies: A Dynamic Structural Approach - David Koll; Dominik Sachs; Fabian Stürmer-Heiber; Hélène Turon (Center for Economic Studies and ifo Institute (CESifo), 2023)
We formalize and estimate the dynamic marginal efficiency cost of redistribution (MECR) in the spirit of Okun's "leaky bucket". We analyze the MECR of an income-contingent childcare subsidy program and the income tax within the German context, using a dynamic structural heterogeneous-household model of childcare demand and maternal labor supply. This allows us to compare which of these two policies is more efficient in achieving redistributive goals. Our analysis identifies two competing forces. (i) Labor supply responses increase the MECR of the childcare subsidy relative to the income tax. (ii) Child development effects decrease the MECR of the childcare subsidy relative to the income tax. For reasonably large Pareto weights on children, we find that (ii) dominates (i) and therefore the childcare subsidy is the more efficient redistribution tool.
Keywords: H23; H31; J13; J22; J24; 330; female labor supply; childcare; family policies; fiscal externalities; dynamic discrete choice; redistribution